Cost-Effectiveness of Thrombectomy in Patients With Acute Ischemic Stroke: The THRACE Randomized Controlled Trial. Issue 10 (October 2017) - Achit, Hamza; Soudant, Marc; Hosseini, Kossar; Bannay, Aurélie; Epstein, Jonathan; Bracard, Serge; Guillemin, Francis
Abstract : Background and Purpose—: The benefit of mechanical thrombectomy added to intravenous thrombolysis (IVT) in patients with acute ischemic stroke has been largely demonstrated. However, evidence of the economic incentive of this strategy is still limited, especially in the context of a randomized controlled trial. We aimed to analyze whether mechanical thrombectomy combined with IVT (IVMT) is cost-effective when compared with IVT alone. Methods—: Individual-level cost and outcome data were collected in the THRACE randomized controlled trial (Thrombectomie des Artères Cerébrales) including patients with acute ischemic stroke. Patients were assigned to receive IVT or IVMT. The primary outcomes were modified Rankin Scale score of functional independence at 90 days (score 0–2) and the EuroQol-5D quality-of-life score at 1 year. Results—: Treating acute ischemic stroke with IVMT (n=200) versus IVT (n=202) increased the rate of functional independence by 10.9% (53.0% versus 42.1%; P =0.028), at an increased cost of $2116 ([Euro sign]1909), with no significant difference in mortality (12% versus 13%; P =0.70) or symptomatic intracranial hemorrhage (2% versus 2%; P =0.71). The cost per one averted case of disability was estimated at $19 379 ([Euro sign]17 480). The incremental cost per one quality-adjusted life year gained was $14 881 ([Euro sign]13 423). On sensitivity analysis, the probability of cost-effectiveness with IVMT was 84.1% in terms of cases of averted disability and 92.2% in terms of quality-adjusted life years. Conclusions—: Based on randomized trial data, this study demonstrates that IVMT used to treat acute ischemic stroke is cost-effective when compared with IVT alone. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01062698.